Some Features of Article 76 Implementation of the United Nations Convention on Contracts for the International Sale of Goods, Vienna, 1980 - Alexander V. Padiryakov (Московский журнал международного права, 2015)
The article focuses on the specific features of recovery of damages incurred as result of non-performance of the international sales contracts, in particular, the international sales contracts with respect to goods between Russian and foreign companies if such contracts are governed by the CISG.